PENGARUH PEMBIAYAAN BERMASALAH DAN EFISIENSI OPERASIONAL TERHADAP PROFITABILITAS PADA BANK SYARIAH INDONESIA PERIODE 2018-2022 - Nilam Utami Aqillah; Ahmad Perdana Indra; Nurul Jannah (JURNAL ILMIAH EDUNOMIKA, 2023)
Ability to generate profit (prof) for Islamic Banks very impactful in increasing the growth of Islamic Banks itself. Islamic commercial banks in generating profits have various products, one of which is Financing. The ratio that can used to see the occurrence of problematic financing using the ratio of Non Performing Financing (NPF). Implementation Islamic bank operations in terms of operational efficiency. Indicator operational banking efficiency in terms of costs is the ratio between operational costs to operating income (BOPO). The method used in this research is quantitative method with data collection techniques one of which uses documents obtained from OJK (Financial Services Authority) in the form of Bank Syariah Indonesia monthly financial reports for the period 2018- 2022. The sample used in this study was 60 financial statements. Data sources were processed using the SPSS version 29 application. The analytical method used was descriptive statistical test, test classical assumptions (normality test, multicollinearity test, autocorrelation test and heteroscedasticity test) and multiple linear regression analysis test. Based on the research results show that financing problem has a significant effect on profitability with based on Islamic business ethics at Bank Syariah Indonesia. Influence operational efficiency partially has a negative or no effect significant effect on profitability in Bank Syariah Indonesia. While simultaneously the effect of troubled financing and jointly significant positive operational efficiency to profiatability represented by multiple regression analysis using the F test